Islamic banking and finance Terms Apps (ibfterms Apps) - Dollah, Nafi@Hanafi; Hassan, Rusni; Mansor, Yushiana; Md Ghalib, Mohd. Feham (Namelite Technology, 2018)
This mobile terminology glossary app was designed by using a developmental research design using via rapid prototype instructional design model. The current project proposes to explore the prototype development and implementations of the mobile accessibility using commonly used mobile platforms i.e. iOS and Android. It is wise to note here that the mobile app for Islamic banking and financial glossary of terms is none to be found in the market nowadays.